The New Aspects of the Economic Relations Between European Union and China - Puślecki, Zdzisław W. (Archives of Business Research, 2015)
In this research work, Author focus on the analysis of the new aspects of the economic relations between European Union and People Republic China. What indicates the importance and innovativeness of the research is the presentation of the technical progress especially in China, the growth of economic ties with the European Union and the benefits resulting from liberalised of the China foreign trade policy under WTO. Accordance to the foreign trade policy theory further trade liberalisation and improved framework policies would increase trade and promote growth. In the new circumstances for the development of the global economy and the global trade, People Republic of China seems to be a production superpower, able to change the world trade and also the European Union’s extra trade. In many areas it possesses comparative advantages. China may continue their development to specialise in electronics and increasingly in services. With or without further trade agreements between two partners, services will be more traded and trade policies will have to adjust to changes in the organisation of global value change. With new investments, a country can transform its position through industrial expansion at home and sustain it through international trade. China is especially sensitive to the advantages of intensive growth and will not wish to disrupt essential economic arrangements that have been crucial to her success. The main aim of the article is the presentation of the new aspects of the economic relations between European Union and China